POLEMIK PELAKSANAAN SHOLAT BERJAMA’AH BERJARAK DIMASA PANDEMI COVID-19 (Ahkam: Jurnal Hukum Islam, 2022)
At the end of 2019 there was the discovery of a new virus that was considered deadly and became a new threat to the world. This virus was first discovered in Wuhan City, Hubei Province, China. WHO (World Health Organization or World Health Organization) on January 30, 2020 announced that the world was currently experiencing a health emergency. The purpose of this study was to find out the legal review related to spacing the rows when performing congregational prayers which is one way to prevent the spread of the Covid-19 Virus. The research method used in this study is a qualitative method with the type of library research (Libraray Research). The sources used in this research are journal articles, fiqh books, news and websites related to the topic of this research. After collecting sources and data, the author analyzes and describes them to arrive at conclusions from discussing the topics in this article. The results of this study are that if in a state of necessity, it is permissible to give the rows a distance, the prayer is valid and does not lose the virtue of praying in congregation. In this case, the forced situation is the Covid-19 pandemic which can spread quickly if people are close to each other. Keywords: Congregational Prayer, Covid-19, PSBB, MUI Fatwa